The string theory landscape - Schellekens, Bert (International journal of modern physics. A, Particles and fields, gravitation, cosmology, 2015)
Perhaps the most important way string theory has affected the perspective of particle physics phenomenology is through the "string theory landscape". We discuss the evidence supporting its existence, describe the regions of the landscape that have been explored, and examine what the string theory landscape might imply for most Standard Model problems.